Cultivation of Tilapia (Oreochromis niloticus) Using Floating Net Cage System to Improve Economic Value of Alur Cucur Community, Rantau, Aceh Tamiang - Agus Putra Abdul Samad; Bustami; Hanafiah; Muhammad Amin; Adi Bejo Suwardi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
This village development program aims to develop Tilapia (Oreochromis niloticus) cultivation using floating net cage system. The main target was tilapia production to increase income for community. This program was conducted for 6 months with the target of Pokdakan Sepakat Makmur located in the village of Alur Cucur. The main problems faced by the group were the lack of knowledge about tilapia cultivation techniques using floating net cage, aquaculture activities are still conventionally in earthen ponds. In addition, the capital stock is lacking, and financial administration records are still weak. The activities carried out include: training on fish rearing techniques, making floating net cages by partners who were accompanied by program implementers, cultivating tilapia in rivers using floating net cages, and distributing partner products. At the end of the activity, an evaluation of the implementation and sustainability of the program was carried out after completion of implementation activities.